Method for preparing hydrophobic Ti / SiO2-coated composite aerogel by micro-droplet template method and application of hydrophobic Ti / SiO2-coated composite aerogel
The hydrophobic Ti/SiO2@template composite aerogel prepared by the micro droplet template method solves the problems of degradation in the presence of polar molecules and irregular pores of hydrophilic aerogels, achieving high selectivity and Highly efficient adsorption of thiophene sulfides, especially in the presence of water or pyridine.
Patent Information
- Application Number
- CN202411524178.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing SiO2 composite aerogel adsorbents are hydrophilic and are susceptible to competitive adsorption by polar molecules, and the pore shape is irregular, affecting the diffusion and selectivity of adsorbents.
The hydrophobic Ti/SiO2@template composite aerogel was prepared by micro droplet template method. The methyl triethoxysilane was used as the silicon source, ethanol and water were used as solvents, and thiophene compounds were used as template solutions to form a uniform micro-liquid. Drops are filled in the SiO2 gel skeleton, and then the template agent is removed, regular pores are formed and tetrabutyl titanate is introduced to form Si-O-Ti bonds to improve hydrophobicity and adsorption properties.
The channel regularity and adsorption performance of the aerogel are improved, and the adsorption selectivity and diffusion efficiency of thiophene sulfides are enhanced, especially in the presence of water or pyridine.
Smart Images

Figure BDA0005108750330000051 
Figure BDA0005108750330000061 
Figure BDA0005108750330000065
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation and processing, and specifically relates to a method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method and application thereof. Background Art
[0002] Aromatics is one of the most basic raw materials in the organic chemical industry. The main products include benzene, toluene, xylene, etc., which account for the second largest share of the market after ethylene and propylene. Aromatics are mainly derived from catalytic reforming and thermal cracking of petroleum hydrocarbons. Sulfides in crude oil will be transferred to aromatic products, which will cause environmental pollution during the use of aromatics, and will poison the catalysts in the subsequent processing of aromatics, reducing the yield of aromatic products. Therefore, aromatic desulfurization has become an important research topic in petrochemicals.
[0003] At present, hydrodesulfurization technology (HDS) is the most widely used deep desulfurization technology in industry. HDS can effectively remove mercaptans, sulfides and disulfides, but HDS is used to remove aromatic sulfides (thiophene and its derivatives) under conditions such as high temperature, high pressure and three times the amount of catalyst. At the same time, the aromatics are hydrogenated and saturated, resulting in a decrease in the yield of aromatic products. In other words, HDS cannot achieve deep desulfurization of aromatic products. Therefore, it is necessary to develop other deep desulfurization technologies. The desulfurization technologies that have been reported include biological desulfurization (BDS), extractive desulfurization (EDS), oxidative desulfurization (ODS) and adsorption desulfurization technology (ADS). Among them, ADS not only has low equipment investment, but also mild operating conditions and is environmentally friendly, and has been widely studied.
[0004] The core of adsorption desulfurization technology lies in the selection of suitable adsorbents (high selectivity, large adsorption capacity, and good regeneration performance). The desulfurization adsorbents that have been reported mainly include zeolite molecular sieves, activated carbon, metal organic frameworks (MOFs), metal oxides, and aerogel materials. Most of the above materials are hydrophilic. When polar substances (such as water or pyridine) exist in the system, the adsorption capacity and selectivity of thiophene sulfides will be significantly reduced.
[0005] Aerogels have been widely studied and applied in the field of adsorption due to their advantages such as high specific surface area, high porosity, and three-dimensional network mesoporous structure. In some previous studies, Chinese patents CN 106590728 A, CN 105709685 A, and CN108893138 A have been used to dope Zr 4+ 、Ag + 、Co + , Cu + 、Al 3+SiO2 composite aerogels made of metal ions have good adsorption effects, but they are also hydrophilic materials and are easily affected by competitive adsorption of polar molecules. In addition, aerogel desulfurization adsorbents also have problems such as wide distribution of mesopore size and irregular pore shape, which affect the diffusion of adsorbates. Summary of the invention
[0006] In view of the defects of the SiO2 composite aerogel desulfurization adsorbent prepared by the above conventional method, the purpose of the present invention is to provide a method and application of preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method. The method uses methyltriethoxysilane as a silicon source, ethanol and water as solvents, and forms a hydrophobic silica gel by a sol-gel method. In order to improve the irregular shape of the hydrophobic silica gel pores, a micro-droplet template method is used in the sol-gel process. The specific principle is that the aliphatic hydrocarbon that dissolves thiophene compounds is a template solution, which is a non-polar solution; and the precursor mixture composed of a silicon source, ethanol and water is a polar solution; the two are immiscible. Under high-speed stirring, the template solution will form uniformly distributed tiny droplets in the precursor mixture solution. In the sol-gel process, these tiny template droplets are uniformly filled in the SiO2 alcohol gel skeleton network. In the subsequent preparation process, the template solution is removed, leaving regular channels similar to the shape of the template droplets in the SiO2 alcohol gel skeleton network, thereby improving the pore regularity of the final aerogel. Methyltriethoxysilane hydrolyzes under the conditions of ethanol and water to form silicon monomers, which contain one CH3 and three Si-OH. CH3 can improve the hydrophobicity of the gel, Si-OH can condense into a gel skeleton, and unreacted Si-OH can be used as an anchor point to graft other groups. Another function of the micro-droplet template is that the S of thiophene in the template solution can form hydrogen bonds with Si-OH, guiding the Si-OH that has not formed a gel skeleton network to enrich the mesoporous gel surface formed by the micro-droplets, laying the foundation for the subsequent formation of highly dispersed Si-O-Ti bonds. The subsequent preparation steps are to replace the SiO2 alcohol gel process with n-hexane, and add tetrabutyl titanate dissolved in anhydrous ethanol in this process. Hexane replacement can reduce the water content in the reaction solvent, slow down the hydrolysis rate of tetrabutyl titanate, effectively form Si-O-Ti bonds with Si-OH on the gel surface, and highly dispersedly grafted on the hydrophobic silica gel surface. Finally, after removing the template microdroplets by solvent washing, pores similar to the shape of the template microdroplets are left in the SiO2 alcohol gel skeleton network, which improves the regularity of the aerogel pores and also allows the Ti species to be highly dispersedly grafted on the gel surface. In addition, the preparation method is simple to operate and the cost of preparing the template is low.
[0007] The specific technical solutions are as follows:
[0008] A method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method, wherein the composite aerogel is prepared by a micro-droplet template method based on a sol-gel combined with a normal pressure drying method, and is characterized in that the specific preparation steps can be divided into:
[0009] 1) preparing a micro-droplet template solution: using aliphatic hydrocarbon to dissolve a certain amount of thiophene compounds to form a template solution, the concentration of the thiophene compounds is 2 mg-S / g, and the template solution is a non-polar solution;
[0010] 2) Preparation of hydrophobic silica gel containing microdroplet template: Methyltriethoxysilane is used as a silicon source and mixed with anhydrous ethanol and water A polar solution is formed, and then a certain amount of non-polar template solution is added, stirred at a speed of 900 r / min, the pH is adjusted to 2, and hydrolyzed for 5 hours, so that methyltriethoxysilane is fully hydrolyzed on the one hand, and the non-polar template solution forms uniform micro-droplets in the above polar solution on the other hand, and then the pH is adjusted to 6.8 with ammonia water, and heated in a water bath to obtain a hydrophobic SiO2@template gel containing a micro-droplet template (aliphatic hydrocarbon solution dissolving thiophene compounds);
[0011] 3) Aging: adding an aging solution composed of ethanol and methyltriethoxysilane to the alcohol gel prepared in step 2), wherein the volume ratio of anhydrous ethanol to methyltriethoxysilane is 25:15, and aging in a water bath at a certain temperature for a period of time to enhance its skeleton structure;
[0012] 4) n-hexane replacement and doping with Ti: grind the gel obtained in step 3) and add n-hexane, dissolve a certain amount of tetrabutyl titanate in anhydrous ethanol, and then add it to the above gel and stir for 5 minutes;
[0013] 5) Removing the micro-droplet template: adding n-hexane to the gel obtained in step 4), washing and replacing with n-hexane, replacing n-hexane every 4 hours, and removing the micro-droplet template;
[0014] 6) Drying: The composite alcohol gel obtained in step 5) is dried at 120° C. under normal pressure to finally obtain a hydrophobic Ti / SiO2@template composite aerogel.
[0015] Furthermore, in step 1), the aliphatic hydrocarbon solution is n-hexane, cyclohexane, n-heptane, n-decane or n-tetradecane, preferably n-heptane.
[0016] Furthermore, the added tetrabutyl titanate is dissolved in anhydrous ethanol, and the molar ratio of the Si element added in step 2) to the Ti element added in step 4) is 80 to 30:1, preferably 60:1.
[0017] Furthermore, the volume ratio of the total volume of ethanol, water and methyltriethoxysilane to the template solution is 20.6:1-8, preferably 20.6:5.
[0018] An application of the hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent prepared by the above preparation method, the specific operation steps are as follows:
[0019] The obtained adsorbent was quantitatively loaded into the adsorption bed device and heated for 2 h. -1 Simulated aromatic hydrocarbons containing thiophene, simulated aromatic hydrocarbons containing thiophene and pyridine, or simulated aromatic hydrocarbons containing thiophene and water are introduced into the adsorber device at a space velocity for adsorption.
[0020] The beneficial effects of the present invention are as follows:
[0021] 1) The hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent of the present invention uses methyltriethoxysilane as the silicon source. The aerogel surface contains methyl groups and has strong hydrophobicity. It is difficult for substances such as water and pyridine to approach the active center. Therefore, when polar molecules such as water or pyridine exist in the simulated aromatic product, the hydrophobic Ti / SiO2@template composite aerogel has high adsorption selectivity for thiophene sulfides.
[0022] 2) The hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent of the present invention introduces tetrabutyl titanate into the construction of the aerogel skeleton network, grafts Ti species, and forms Si-O-Ti bonds. In the aerogel, Ti can serve as a Leis acid center to form an acid-base adsorption effect with thiophene sulfides, thereby enhancing the adsorption and desulfurization performance of the composite aerogel.
[0023] 3) The micro-droplet template method proposed by the hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent of the present invention (using the micro-droplets formed by stirring n-heptane in a polar solvent in which thiophene compounds are dissolved as a template) is used to regularize the pores of the Ti / SiO2@template composite aerogel desulfurization adsorbent modified by Ti, thereby improving the diffusion efficiency of the adsorbent and the adsorption performance. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0025] Examples 1 to 5: Preparation of hydrophobic Ti / SiO2@template composite aerogel adsorbents using different micro-droplet template compositions.
[0026] Example 1: When the silicon / nitrogen molar ratio is 60:1, a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent is prepared by a micro-droplet template method, and the preparation method steps are as follows:
[0027] 1) dissolving thiophene in cyclohexane to prepare a mixed solution with a concentration of 2 mg-S / g, which is used as a microdroplet template solution;
[0028] 2) 10 mL of anhydrous ethanol, 4.6 mL of methyltriethoxysilane, 6 mL of deionized water and 5 mL of template solution were added. The mixture was mixed thoroughly, stirred at 900 r / min, the pH was adjusted to 2, and the mixture was hydrolyzed for 5 h. The pH was then adjusted to 6.8 with aqueous ammonia, and the mixture was heated in a water bath at 50°C for 2 h to obtain a hydrophobic SiO2@template gel containing a microdroplet template (a cyclohexane solution of dissolved thiophene sulfides).
[0029] 3) Add 25 ml of anhydrous ethanol and 15 ml of n-methyltriethoxysilane to the composite alcohol gel obtained in step 2), and place in a 50° C. water bath for aging for 15 hours to enhance the skeleton structure of the gel.
[0030] 4) Grind the gel obtained in step 3) and add 100 mL of n-hexane, dissolve 0.130 mL of tetrabutyl titanate in anhydrous ethanol (Si / Ti molar ratio is 60:1), then add the mixture to the gel and stir for 5 min;
[0031] 5) Removing the micro-droplet template: adding n-hexane to the gel obtained in step 4), washing and replacing with n-hexane, replacing the n-hexane every 4 hours, and replacing 3 times to remove the micro-droplet template;
[0032] 6) Drying: The composite alcohol gel obtained in step 5) is dried at 120° C. under normal pressure to finally obtain a hydrophobic Ti / SiO2@template composite aerogel.
[0033] Examples 2 to 5: The preparation method is the same as that of Example 1, except that the template solution selected in step 1) is a thiophene solution dissolved in n-hexane, n-heptane, n-decane, or n-tetradecane, respectively.
[0034] Fill the bottom of a glass tube of a certain length with absorbent cotton, then add 1g of fresh hydrophobic Ti / SiO2@template prepared in Examples 1-5, and then add an appropriate amount of quartz sand on top of the adsorbent. Fully wet the filled adsorbent with n-heptane, and then heat for 2h. -1Simulated aromatic hydrocarbon MA-1 (MA-1: thiophene with a sulfur concentration of 2 mg-S / g dissolved in p-xylene to obtain simulated aromatic hydrocarbon MA-1) was introduced at a space velocity of 1.5 %. The simulated aromatic hydrocarbon after adsorption was collected at the lower end of the adsorber and chromatographically analyzed. The breakthrough point was determined when the sulfur concentration in the effluent was 0.005 mgS / g. The adsorption results are shown in Table 1.
[0035] Table 1 Effect of different microdroplet template compositions on the adsorption performance of hydrophobic Ti / SiO2@template composite aerogels for thiophene in simulated aromatic hydrocarbons
[0036]
[0037] It can be seen from Table 1 that among the different micro-droplet template compositions, as the molecular weight of the aliphatic hydrocarbon increases, the penetration adsorption capacity of the hydrophobic Ti / SiO2@template composite aerogel for thiophene compounds first increases and then decreases. When thiophene is dissolved in n-heptane as a micro-droplet template, the penetration adsorption capacity of the hydrophobic Ti / SiO2@template composite aerogel for thiophene is the highest. Therefore, thiophene dissolved in n-heptane is preferably used as a micro-droplet template to prepare the hydrophobic Ti / SiO2@template composite aerogel.
[0038] Examples 7-10: Effect of silicon / titanium molar ratio on the adsorption performance of hydrophobic Ti / SiO2@template composite aerogels for thiophene sulfides in simulated aromatic hydrocarbons.
[0039] The preparation method is the same as that of Example 3, except that in step 4), 0.196 mL, 0.156 mL, 0.112 mL and 0.098 mL of tetrabutyl titanate are added, respectively, so that the Si / Ti molar ratios of Examples 7 to 10 are 40:1, 50:1, 70:1 and 80:1, respectively.
[0040] The evaluation method of the adsorbent prepared in Examples 7 to 10 is the same as that in Example 6, and the specific results are shown in Table 2. Table 2 Effect of silicon / titanium molar ratio on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons by hydrophobic Ti / SiO2@template composite aerogel
[0041]
[0042] It can be seen from Table 2 that with the increase of silicon / titanium molar ratio (the decrease of Ti doping amount), the penetration adsorption capacity of hydrophobic Ti / SiO2@template composite aerogel for thiophene compounds first increases and then decreases, among which the silicon / nitrogen molar ratio of 60:1 is the most preferred.
[0043] Examples 11-14: Effect of the amount of template solution added on the adsorption performance of thiophene compounds in simulated aromatic products by the hydrophobic Ti / SiO2@template composite aerogel adsorbent prepared by the microdroplet template method.
[0044] The silicon / nitrogen molar ratio was fixed at 60:1, and the preparation steps were the same as those in Example 3, except that the amount of microdroplet template added in step 2) was 3 ml, 4 ml, 6 ml, and 7 ml, respectively. In Examples 11 to 14, They are 20.6:3, 20.6:4, 20.6:6 and 20.6:7 respectively.
[0045] Comparative Example 1: The preparation method is the same as that of Example 3, except that the micro-droplet template solution prepared in step 1) is not required to be added in step 2).
[0046] Table 3 Effect of the amount of template solution added on the adsorption performance of thiophene compounds in simulated aromatic products by hydrophobic Ti / SiO2@template composite aerogel adsorbent prepared by microdroplet template method
[0047]
[0048]
[0049] It can be seen from Table 3 that with As the amount of micro-droplet template solution increases, the penetration adsorption capacity of the hydrophobic Ti / SiO2@template composite aerogel for thiophene compounds increases first and then decreases. When the ratio is 20.6 / 5, the penetration adsorption capacity of thiophene compounds reaches the maximum. Compared with the comparative example 1 without adding the template solution, the hydrophobic Ti / SiO2@template composite aerogel prepared by the micro-droplet template method has a better adsorption effect on thiophene compounds. This is attributed to the fact that the addition of the micro-droplet template makes the pores in the aerogel skeleton more regular, thereby improving the diffusion performance of the adsorbate. In addition, the S atoms in the thiophene compounds in the micro-droplet template can guide -Si-OH, Ti 4+ The adsorption active sites are enriched on the inner surface of the aerogel skeleton and are fully exposed, thereby improving the adsorption capacity.
[0050] Examples 15-17: Effect of the adsorption performance of thiophene compounds on the hydrophobic Ti / SiO2@template composite aerogel adsorbent prepared by the microdroplet template method in the presence of water and pyridine in simulated aromatic hydrocarbons.
[0051] The adsorbent used is the same as that in Example 3, and its breakthrough adsorption experiment is the same as that in Example 6, except that the simulated aromatic hydrocarbons used are MA-1, MA-2 and MA-3 respectively (MA-2: thiophene with a sulfur concentration of 2 mg-S / g dissolved in p-xylene, and then 1%wt of water is added as a competitive adsorbent; MA-3: thiophene with a sulfur concentration of 2 mg-S / g dissolved in p-xylene, and then 1%wt of pyridine is added as a competitive adsorbent).
[0052] Comparative Example 2: The preparation method is the same as that of Example 3, except that in Comparative Example 1, the methyltriethoxysilane solvent in step 1) and step 2) is replaced with an ethyl orthosilicate solvent, and 8 mL of ethyl orthosilicate and 2 mL of H2O are added to step 1), and 0.130 mL of tetrabutyl titanate is added to step 4) to prepare a hydrophilic Ti / SiO2@template composite aerogel adsorbent with a silicon / titanium molar ratio of 60:1. The simulated aromatic hydrocarbon used is MA-1, and the penetration adsorption results are shown in Table 4.
[0053] Comparative Examples 3-4: The preparation method is the same as that of Comparative Example 2, and the penetration adsorption experiment is the same as that of Example 6, except that the simulated aromatic hydrocarbons used are MA-2 and MA-3, respectively. The penetration adsorption results are shown in Table 4.
[0054] ,Table 4 Adsorption performance of hydrophobic Ti / SiO2@template composite aerogel adsorbent prepared by microdroplet template method for thiophene compounds in the presence of water and pyridine in simulated aromatic hydrocarbons
[0055]
[0056]
[0057] It can be seen from Table 4 that when there is 1% water in the simulated aromatic hydrocarbons, the penetration adsorption capacity of both types of aerogel adsorbents for thiophene decreases, but the adsorption performance of the hydrophilic Ti / SiO2@template composite aerogel prepared by the microdroplet template method for thiophene sulfides is significantly reduced, with a reduction of up to 19.9%, while the penetration adsorption performance of the hydrophobic Ti / SiO2@template composite aerogel prepared by the microdroplet template method is slightly reduced, only by 1.6%, and the hydrophobic Ti / SiO2@template composite aerogel has a higher penetration adsorption capacity for thiophene in the simulated aromatic hydrocarbons. Similarly, the presence of pyridine in simulated aromatic hydrocarbons will reduce the penetration adsorption capacity of the aerogel adsorbent for thiophene, and the presence of pyridine has a greater impact on the adsorption capacity than the presence of water in simulated aromatic hydrocarbons. However, compared with the hydrophilic Ti / SiO2@template composite aerogel, when pyridine is present in the simulated solution, the adsorption capacity of the hydrophobic Ti / SiO2@template composite aerogel adsorbent for thiophene in simulated aromatic hydrocarbons decreases much less, so the hydrophobic Ti / SiO2@template composite aerogel has higher polarity resistance.
Claims
1. A method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method, wherein the composite aerogel is prepared by a micro-droplet template method based on a sol-gel combined with a normal pressure drying method, and is characterized in that: The specific preparation steps can be divided into: 1) preparing a micro-droplet template solution: dissolving a thiophene compound in an aliphatic hydrocarbon to form a template solution, wherein the concentration of the thiophene compound is 2 mg-S / g, and the template solution is a non-polar solution; 2) Preparation of a hydrophobic silica gel containing a micro-droplet template: methyltriethoxysilane is used as a silicon source, mixed with anhydrous ethanol and water to form a polar solution, and then the non-polar template solution prepared in step 1) is added, stirred at a speed of 900 r / min, the pH is adjusted to 2, and hydrolyzed for 5 hours, on the one hand, the methyltriethoxysilane is fully hydrolyzed, and on the other hand, the non-polar template solution forms uniform micro-droplets in the above polar solution, and then the pH is adjusted to 6.8 with ammonia water, and heated in a water bath to obtain a hydrophobic SiO2@template gel containing a micro-droplet template; 3) Aging: adding an aging solution composed of ethanol and methyltriethoxysilane to the alcohol gel prepared in step 2), wherein the volume ratio of anhydrous ethanol to methyltriethoxysilane is 25:15, and water bath aging is performed to enhance its skeleton structure; 4) n-hexane replacement and doping with Ti: grind the gel obtained in step 3) and add n-hexane, dissolve tetrabutyl titanate in anhydrous ethanol, and then add it to the above gel and stir; 5) Removing the micro-droplet template: adding n-hexane to the gel obtained in step 4), washing and replacing with n-hexane, replacing n-hexane every 4 hours, and removing the micro-droplet template; 6) Drying: The composite alcohol gel obtained in step 5) is dried at 120° C. under normal pressure to finally obtain a hydrophobic Ti / SiO2@template composite aerogel.
2. The method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method according to claim 1, characterized in that: The aliphatic hydrocarbon in step 1) is n-hexane, cyclohexane, n-heptane, n-decane or n-tetradecane, preferably n-heptane.
3. The method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method according to claim 1, characterized in that: The molar ratio of the Si element added in step 2) to the Ti element added in step 4) is 80 to 30:1, preferably 60:
1.
4. The method for preparing a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent by a micro-droplet template method according to claim 1, characterized in that: In step 2), the volume ratio of anhydrous ethanol, water and methyltriethoxysilane is 10:6:4.6, and the volume ratio of the total volume of ethanol, water and methyltriethoxysilane to the volume of the template solution is 20.6:1-8, preferably 20.6:
5.
5. An application of a hydrophobic Ti / SiO2@template composite aerogel desulfurization adsorbent prepared by the method according to any one of claims 1 to 5, characterized in that: The specific operation steps are as follows: quantitatively load the obtained adsorbent into the adsorption bed device for 2 hours. -1 Simulated aromatic hydrocarbons containing thiophene, simulated aromatic hydrocarbons containing thiophene and pyridine, or simulated aromatic hydrocarbons containing thiophene and water are introduced into the adsorber device at a space velocity for adsorption.
Citation Information
Cited By
Method for preparing hydrophobic La-Al / SiO2 composite aerogel desulfurization adsorbent by micro-droplet template method and application of hydrophobic La-Al / SiO2 composite aerogel desulfurization adsorbent
CN122164361A